Lincoln and the U.S. Colored Troops - Smith, John David, 1949- (Book collections on Project MUSE., 2013)
When Abraham Lincoln issued his final Emancipation Proclamation on January 1, 1863, he not only freed the slaves in the Confederate states but also invited freed slaves and free persons of color to join the U.S. Army as part of the U.S. Colored Troops (USCT), the first systematic, large-scale effort by the U.S. government to arm African Americans to aid in the nation's defense. By the end of the war in 1865, nearly 180,000 black soldiers had fought for the Union. Lincoln's role in the arming of African Americans remains a central but unfortunately obscure part of one of the most compellin.